UNDERSTANDING CLIMATE CHANGE TOPICS CRITICALLY THROUGH ANDROID-BASED MODULE FOR STUDENT - Anggraeni, Titis Nindiasari; Aminatun, Tien (Curriculum and Educational Technology Department, 2019)
Climate change is urgent world issue that should be face critically by student. This article tries to illustrate one effort to improve student critical thinking skill toward climate change topics through developing Android-based learning module. By employing design and development research (DDR) approach this research using Search, Solve, Create, and Share (SSCS) learning model on producing the module. In the end of the process the module is ready for use because the comparison between experimental class and control class indicates that there is an increasing of student critical thinking skills when they use the module. Therefore, Android and others technological product should be recognize as having huge potential to encourage student awareness and critical thinking toward climate change issues. Abstrak Perubahan iklim adalah masalah dunia yang mendesak yang harus dihadapi secara kritis oleh siswa. Artikel ini menggambarkan satu upaya meningkatkan keterampilan berpikir kritis siswa terhadap topik-topik perubahan iklim dalam mata pelajaran di sekolah melalui pengembangan modul pembelajaran berbasis Android. Dengan menggunakan pendekatan Design & Development Research (DDR) penelitian ini menggunakan model pembelajaran Search, Solve, Create, dan Share (SSCS) dalam pengembangan modulnya. Pada akhir proses, modul siap digunakan karena perbandingan antara kelas eksperimen dan kelas kontrol menunjukkan bahwa ada peningkatan keterampilan berpikir kritis siswa ketika mereka menggunakan modul tersebut. Dengan demikian, Android dan produk teknologi lainnya harus diakui memiliki potensi besar untuk mendorong kesadaran dan daya kritis siswa terhadap masalah perubahan iklim.